Improvement Printing Industry Plant layout for Effective Production - Watanapa, A; Wiyaratn, W; Kajondecha, P (Lecture notes in engineering and computer science, 2014)
This research was aimed at planning the layout of the factory and the location of additional machine to increase the productivity based on the systematic layout planning pattern (SLP) to design a virtual model of the factory to meet the maximum requirements of the factory extension. There were 9 models for the layout planning and only one best model would be chosen according to the suitability and the practicalities for the printer. 3 potential models were analyzed and it was found that Model A-3 has become the best one which met most of the practicalities. The working time would be 1.592 hour and the length of work would be 384.618 meters in total.